Meaning in Life for people who have experienced a First Episode Psychosis: An Interpretative Phenomenological Analysis - O'KEEFFE, DONAL PADRAIG (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2019)
Background: The concept of Meaning in Life (MIL) is understood to be central aspect of service user defined recovery in mental health. MIL takes on renewed importance in the context of widespread endorsement of the recovery approach in mental health; as service development and reform are required to prioritise service user defined recovery. Psychosis appears to impact the degree to which a person experiences MIL. However, there is little research available that helps us understand how MIL is experienced in recovery in psychosis or how meaning making in psychosis experiences influences a person's perspective on MIL. Aim: The aim of this study was to explore how people who experienced a First Episode Psychosis (FEP) approximately 21 years ago find, develop, and maintain MIL and identify the key factors that influence MIL. Methodology: This qualitative study used Interpretative Phenomenological Analysis (IPA) and adopted a multiperspectival design. Participants were recruited from a cohort of people diagnosed with a FEP between February 1995 and February 1999. The study was carried out within a public/private mental health service based in Dublin in Ireland. Semi-structured interviews were conducted with 16 participants: 8 people In Remission and 8 people Not in Remission from psychosis, who were recruited using purposive sampling. Data were analysed according to IPA principles. Findings: Data were coded as relating to either Meaning making in psychosis experiences or Meaning in life in the context of mental health recovery. Meaning making in psychosis experiences formed the context and backdrop for participants finding, developing, and maintaining MIL in the recovery journey. Five themes were developed to encompass Meaning making in psychosis experiences. Firstly, psychosis experiences were found to erode MIL. This is reflected in the first three themes: Theme 1 Living with the impact of psychosis on the self and identity; Theme 2 Reconnecting with time to move forward in time; and Theme 3 Navigating agency and powerlessness in chaos. Psychosis experiences were understood to threaten or damage a person's self, preferred identity, relationship with time, and control in their lives. Secondly, psychosis experiences were found to contribute to MIL by adding something that was not present in the person's life prior to psychosis (Theme 4 Generating Meaning in Life in a vacuum). Psychosis experiences offered a path to: establishing connection and understanding; contributing something of value to society; realising potential; and exceptionality. Thirdly, psychosis experiences disrupted narrative coherence and blocked the ability to narrate parts of life (Theme 5 Trying to find a home for psychosis or not needing to). Five themes were developed to capture Meaning in life in the context of mental health recovery. Participants found, developed, and maintained MIL by being aware of their connectedness to their context. Experiencing MIL through connectedness to context occurred in five main ways represented by five themes. Theme 1 Being myself – de-othering and authenticity involved participants being cognisant that they resided in a self (their identity). They sought to enact their identity by pursuing congruence between their true self and their actions. Theme 2 Becoming significant where the self is witnessed involved participants acknowledging that the self existed in relation to the self and others. They aimed to belong amid their life witnesses (including the self) to experience significance. Theme 3 Generating meaning within and beyond systems involved participants realising that the self existed in relation to systems. They used systems to generate MIL but also attained MIL from transcending them. Theme 4 Shaping and being shaped by life involved participants appreciating how their environment shaped the self and the self shaped their environment. Finally, Theme 5 Integrating different perspectives of time involved participants developing an awareness of how the self was experienced across time. They had to acknowledge that temporality changes depending on life circumstances. Conclusion: The findings provide novel insight into the complexity of how MIL is experienced by people who have personally encountered psychosis. They also illuminate the influence of meaning making in psychosis experiences on MIL. The findings enhance the conceptual clarity of MIL in the context of mental health recovery in psychosis and contribute to meaning making and mental health recovery theory. In so doing, they also offer guidance for education, clinical practice, service provision, and future research and have practical relevance for therapeutic engagement, trauma informed care, and the recovery approach.
APPROVED
Keywords: mental health recovery; psychosis; meaning in life; meaning making; the recovery approach; therapeutic engagement; interpretative phenomenological analysis